A dualidade na formação no ensino profissionalizante em um ambiente de aprendizagem de modelagem matemática - Celio Roberto Melillo (2017)
In this work, I intend to discuss how duality general training / technical training in Federal Institutes of Education, Science and Technology is expressed in a mathematical modeling learning environment. My annoyance with the prevailing dualism in vocational education in schools where I worked was the starting point for this research. I searched for a greater understanding of the issues involved in this matter, making a historical trajectory of vocational education in Brazil, discussing the influences, interests and the consequences of various stages, from the creation of Apprentices Schools Craftsmen to the Federal Institutes of Education , Science and technology. I used the unitary school notion of Antonio Gramsci to position myself before a dualist school, to be featured in the work, and its anti-democratic and segregating aspects. Also I instructed me in educational principles of John Dewey, especially regarding the importance of adopting themes and teaching methods that emphasize integration between acting and thinking. In the context of mathematics education, worked out a mathematical modelling learning environment guided by the precepts of Critical Mathematics Education, according to Ole Skovsmose as context to trigger discussions on the issue of duality in the context of a pedagogical practice developed in a mathematics classroom a Federal Institute. The data collected from this field research, captured in audio recordings, video, written reports and interviews will be analyzed using a qualitative approach, seeking, in the actions and speeches of the subjects, all of which contribute to a meaning (or reframing) duality when participating in a modelling environment in critical perspective. Some aspects of duality seem to appear in a peculiar way in the learning environment, which is analyzed in terms of student dialogues and actions, using Helle Alrø and Ole Skovsmose's "dialogic actions." I develop the understanding that mathematical modeling lights up the question of duality, which manifests itself in different forms in the actions and trials of the subjects studied. The communications assume new meanings by the use of the technology, the research dynamics and the study subjects by the students, bringing to the fore that duality seems to be rooted both in school practices and in social relationships in which students are involved.